Medicinal Plant Studies Influenced By The Biotechnological Methods: An Updated Review - PANKAJ NAINWAL,; RANVEER BATSA,; AMANDEEP SINGH,; DEEPAK NANDA, (International Journal of Pharma and Bio Sciences, 2011)
Medicinal plants are the most important source of life saving drugs for the majority of the world’s population. The biotechnological tools are important to select, multiply and conserve the critical genotypes of medicinal plants. In-vitro regeneration holds tremendous potential for the production of high-quality plant-based medicine. Cryopreservation is long-term conservation method in liquid nitrogen and provides an opportunity for conservation of endangered medicinal plants. In-vitro production of secondary metabolites in plant cell suspension cultures has been reported from various medicinal plants. Bioreactors are the key step towards commercial production of secondary metabolites by plant biotechnology. Genetic transformation may be a powerful tool for enhancing the productivity of novel secondary metabolites; especially by Agrobacterium rhizogenes induced hairy roots. This article discusses the applications of biotechnology for regeneration and genetic transformation for enhancement of secondary metabolite production in-vitro from medicinal plants.